Biographical research through the looking glass of social distancing: Reflections on biographical interviewing and online technologies in pandemic times - Moran, L. (2022)
This paper asks critical questions about biographical interviewing during the coronavirus disease 2019 era and the age of social distancing. How do we ‘do’ biographical research when we are more physically distant from interview participants than ever before? What kinds of challenges and issues emerge when doing biographical research in online spaces? How do we form rapport and strong trusting bonds with interviewees in the current context? This paper provides a critical commentary on these questions, focusing on the limitations and possibilities of online interviewing during pandemic times.